2016
DOI: 10.1016/j.bjm.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Use of homologous recombination in yeast to create chimeric bovine viral diarrhea virus cDNA clones

Abstract: The open reading frame of a Brazilian bovine viral diarrhea virus (BVDV) strain, IBSP4ncp, was recombined with the untranslated regions of the reference NADL strain by homologous recombination in Saccharomyces cerevisiae, resulting in chimeric full-length cDNA clones of BVDV (chi-NADL/IBSP4ncp#2 and chi-NADL/IBSP4ncp#3). The recombinant clones were successfully recovered, resulting in viable viruses, having the kinetics of replication, focus size, and morphology similar to those of the parental virus, IBSP4ncp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…CHIKV remains a potential threat to public health with no specific antiviral available [ 9 ]. In this study, we successfully constructed a replicative CHIKV reporter replicon using homologous recombination in yeast, a strategy previously used to obtain reverse genetics systems for RNA viruses, such as dengue, yellow fever, bovine viral diarrhea virus and infectious bursal disease virus (IBDV) [ 29 , 32 , 33 , 34 ]. A BHK-21 cell line expressing the GLuc-Neo-CHIKV system, the BHK-21-GLuc-nsP-CHIKV-99659, was developed and demonstrated to persistently express the replicon RNA with no change in GLuc activity over 10 passages.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV remains a potential threat to public health with no specific antiviral available [ 9 ]. In this study, we successfully constructed a replicative CHIKV reporter replicon using homologous recombination in yeast, a strategy previously used to obtain reverse genetics systems for RNA viruses, such as dengue, yellow fever, bovine viral diarrhea virus and infectious bursal disease virus (IBDV) [ 29 , 32 , 33 , 34 ]. A BHK-21 cell line expressing the GLuc-Neo-CHIKV system, the BHK-21-GLuc-nsP-CHIKV-99659, was developed and demonstrated to persistently express the replicon RNA with no change in GLuc activity over 10 passages.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the positively identified recombinant strain, cultivated on the YPD plate with 210 μg/mL G418 antibiotic, was subcultured onto a YPD plate containing 420 μg/mL G418 antibiotic for re-screening. Under these conditions, the false positive strain failed to grow [34] . Similarly employed homologous recombination to construct a chimeric Brazilian bovine viral diarrhea virus (BVDV) cDNA clone in S. cerevisiae, confirming that the chimeric virus remained stable in cell cultures for at least 10 generations, maintaining its replication efficiency intact.…”
Section: Generation Of Pox1 Deletion Strainsmentioning
confidence: 99%
“…The data showed that rHCLV-uspCap and rHCLV-pspCap rather than rHCLV-2ACap elicited detectable anti-Cap antibodies in rabbits, which demonstrated that C-strain could be used as a viral vector to develop bivalent vaccines [ 122 ]. Furthermore, it has been shown that the recombinant BVDV expressing the PEDV spike protein, as a recombinant virus vector, can induce higher titers of NAbs and provide protection against virulent challenge [ 128 , 134 ].…”
Section: Development Of Multivalent Vaccines Based On Pestivirusesmentioning
confidence: 99%